Acute Bronchitis Caused by Bordetella Pertussis Possibly Co-Infected with Mycoplasma Pneumoniae - Kazama, Itsuro (Am J Case Rep, 2019)
Patient: Female, 49 Final Diagnosis: Acute bronchitis caused by Bordetella pertussis Symptoms: Persistent productive cough Medication: — Clinical Procedure: Antibitotics treatment Specialty: Infectious Diseases OBJECTIVE: Rare co-existance of disease or pathology BACKGROUND: Mycoplasma pneumoniae and Bordetella pertussis are among the causative pathogens of human acute bronchitis, which usually has mild symptoms. However, if there is a co-infection, the symptoms often can be prolonged and occasionally can lead to severe respiratory complications. CASE REPORT: A 49-year-old Japanese female, who had not been vaccinated for B. pertussis, developed a persistent productive cough which became vigorous, and occasionally caused difficulty breathing and vomiting. Since serum IgM to M. pneumoniae was positive and IgG to B. pertussis was significantly elevated, and there were no findings of pneumonia on a chest x-ray film, we made a diagnosis of acute bronchitis caused by B. pertussis with possible co-infection with M. pneumoniae. The use of garenoxacin, a quinolone derivative, failed to work; however, a macrolide antibiotic clarithromycin dramatically improved her symptoms shortly after its administration. CONCLUSIONS: In this patient case, because of the lymphocyte-stimulatory nature of M. pneumoniae and B. pertussis, an increased immunological response was likely to be involved in the pathogenesis of the symptoms. The immunosuppressive effect of clarithromycin was considered to repress the increased lymphocyte activity, facilitating the remission of the disease.